Swelling pressure of montmorillonite with multiple water layers at elevated temperatures and water pressures: A molecular dynamics study - Yang, Yafan; Qiao, Rui; Wang, Yifeng; Sun, Shuyu (Applied clay science, 2021)
The swelling of clay at high temperature and pressure is important for applications including nuclear waste storage but is not well understood. A molecular dynamics study of the swelling of Na montmorillonite in water at several temperatures (T = 298, 400, and 500 K) and water environment pressures (Pe = 5 and 100 MPa) is reported here. Adopting a rarely used setup that enables swelling pressure to be resolved with an accuracy of ~1 MPa, the swelling pressure was computed at basal spacings 1.6–2.6 nm (or 2–5 water layers between neighboring clay sheets), which has not been widely studied before. At T = 298 K and Pe = 5 MPa, swelling pressure Ps oscillates at d-spacing d smaller than 2.2 nm and decays monotonically as d increases. Increasing T to 500 K but keeping Pe at 5 MPa, Ps remains oscillatory at small d, but its repulsive peak at d = 2.2 nm shifts to ~2.0 nm and Ps at different d-spacings can grow more attractive or repulsive. At d > 2.0 nm, Ps is weakened greatly. Keeping T at 500 K and increasing Pe to 100 MPa, Ps recovers toward that at T = 298 K and Pe = 5 MPa, however, the repulsive peak at d = 2.0 nm remains the same. The opposite effects of increasing temperature and pressure on the density and dielectric screening of water, which control ion correlations and thus double layer repulsion, are essential for understanding the observed swelling pressure at elevated temperatures and its response to environment pressures. •An accurate molecular dynamics setup for determing swelling pressure of clay was used.•Interplay of hydration and double layer force controls swelling pressure of bentonite.•Effects of temperature on swelling pressure vary with d-spacing and water pressure.•Swelling pressure was understood by analyzing water density and dielectric screening.